2019
DOI: 10.1186/s12974-019-1468-6
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage migration inhibitory factor facilitates prostaglandin E2 production of astrocytes to tune inflammatory milieu following spinal cord injury

Abstract: Background Astrocytes have been shown to produce several pro- and anti-inflammatory cytokines to maintain homeostasis of microenvironment in response to vast array of CNS insults. Some inflammation-related cytokines are responsible for regulating such cell events. Macrophage migration inhibitory factor (MIF) is a proinflammatory cytokine that can be inducibly expressed in the lesioned spinal cord. Unknown is whether MIF can facilitate the production of immunosuppressive factors from astrocytes to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 62 publications
4
67
0
Order By: Relevance
“…While this implies that the microenvironment may change, which would support tumor growth due to prostaglandin production by COX-2 enzymatic activity, other mechanisms are possible. Decreased levels of COX-2 are relative to the abnormal immune function of macrophages (17,18). In the present study, it was revealed that KLF9, a direct target of GCs, could reduce LPS-induced COX-2 levels, indicating that KLF9 is a potent inhibitor of immune function in macrophages.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…While this implies that the microenvironment may change, which would support tumor growth due to prostaglandin production by COX-2 enzymatic activity, other mechanisms are possible. Decreased levels of COX-2 are relative to the abnormal immune function of macrophages (17,18). In the present study, it was revealed that KLF9, a direct target of GCs, could reduce LPS-induced COX-2 levels, indicating that KLF9 is a potent inhibitor of immune function in macrophages.…”
Section: Discussionsupporting
confidence: 50%
“…Inhibition of COX-2 may suppress the development of epithelial cell malignancies in the gastrointestinal tract (12)(13)(14). In addition, COX-2 has been revealed to modulate the fate of colon cancer cell lines by generating prostanoids (15)(16)(17). These observations indicate that COX-2 expression and prostanoid generation may play a fundamental role in the initiation and promotion of cancers arising from inflamed tissues, such as cholangiocarcinoma (18).…”
Section: Introductionmentioning
confidence: 99%
“…After SCI, reactive astrocytes, microglia and peripheral immune cells release proinflammatory cytokines and interact with each other, which contributes to the inflammation in the acute and subacute stage (Escartin et al, 2019). Reactive astrocytes also have negative feedback regulation for inflammation after SCI (Haan et al, 2015;Zhang et al, 2019). In summary, the glial scar and reactive astrocytes are not mere limiters of the inflammation but rather balancers which are not only limiting but also contributing to the inflammation.…”
Section: Beneficial Rolesmentioning
confidence: 99%
“…MIF stimulation also increased PTGS2 mRNA expression and PGE 2 secretion in microglial cells 29) . Furthermore, MIF was found to promote PGE 2 production from astrocytes after spinal cord injury 30) . These reports collectively suggest that MIF acts as an inflammatory cytokine that initiates the arachidonic acid cascade, thereby being involved in the regulation of the inflammatory environment.…”
Section: Discussionmentioning
confidence: 96%